Variability and Intra-Specific Classification of Lima Bean (Phaseolus lunatus L.) from Timor Island based on Morphological Characters - Emilia Juliyanti Bria; E. Suharyanto; Purnomo Purnomo (Journal of Tropical Biodiversity and Biotechnology, 2019)
Lima bean (Phaseolus lunatus L.) is a species of beans which originating from the regions of Central America and Andes Mountains. Lima bean in Timor Island is underutilized although these plant growth there and have many variations. This study aims to determine the diversity of lima beans on Timor Island based on morphological characters. Samples were collected by survey methods from three districts on the island of Timor. Morphological traits related to the vegetative and flowering stages and mature seeds morphology were scored using the International Plant Genetic Resources Institute lima bean descriptors with a soft modification. The similarity index is calculated using the General Similarity Coefficient Gower formula. The dendogram is generated from cluster analysis using the Unweighted Pair Group Methods using Arithmetic Average (UPGMA) method. Furthermore, Principal Component Analysis (PCA) was used to determine the role of each morphological character used. The dendogram shows that 23 collected accessions are divided into two main clusters with a 57% similarity index. The two clusters are distinguished based on the presence or absence of secondary colors and secondary patterns in the seed organs. Then, each main cluster is divided into two subclasses based on the character of the pigmentation stem, the length of the terminal leaflets, flower color, and seed type.